Contemplation of tone mapping operators in high dynamic range imaging - Ahmad, Kursheed; Mittal, Sumit; Olanrewaju, Rashidah Funke (International Journal of Emerging Trends & Technology in Computer Science (IJETTCS), 2016)
The technique of tone mapping has found widespread popularity in the modern era owing to its applications in the digital world. There are a considerable number of tone mapping techniques that have been developed so far. One method may be better than the other in some cases which is determined by the requirement of the user. In this paper, some of the techniques for tone mapping/tone reproduction of high dynamic range images have been contemplated. The classification of tone mapping operators has also been given. However, it has been found that these techniques lack in providing quality of service visualization of high dynamic range images. This paper has tried to highlight the drawbacks in the existing traditional methods so that the tone-mapped techniques can be enhanced.